2000
DOI: 10.1002/1098-2795(200008)56:4<465::aid-mrd4>3.3.co;2-h
|View full text |Cite
|
Sign up to set email alerts
|

Porcine leptin receptor: Molecular structure and expression in the ovary

Abstract: The porcine leptin receptor complementary DNA was cloned and sequenced and the leptin receptor gene expression evaluated in the porcine ovary. An open reading frame of 3498 nt cDNA was amplified from pig liver mRNA by RT-PCR. Sequence homology with the extracellular, transmembrane, and cytoplasmic domains of human, mouse, rat, sheep, and cow leptin receptors varied between 45% and 90%. Leptin receptor mRNA was present in porcine kidney, liver, spleen, lung, brain, testis, uterus, ovary, corpus luteum (CL), the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
39
1
1

Year Published

2007
2007
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(44 citation statements)
references
References 0 publications
3
39
1
1
Order By: Relevance
“…Viability of hepatocytes isolated by low speed centrifugation was 89 ± 2.5% by Trypan blue dye exclusion and aliquots were frozen at −80 • C until used. Cytosol and membrane fractions were prepared by centrifugation and differential solubilization in octylglucoside as described by Ruiz-Cortés et al [12]. Purified hepatocytes from the three pigs were thawed on ice, pooled, homogenized by brief exposure to ultrasound in buffer [2 mM octylglucoside, 1 mM DEDTC, 10 mM EDTA in 50 mM Tris, pH 8] and centrifuged at 30,000 g for 60 min at 4 • C. The supernatant (cytosol) was harvested and the particulate fraction was solubilized by ultrasound in 20 mM Tris containing 50 mM EDTA, 0.1 mM DEDTC and 32 mM octylglucoside, and centrifuged at 16,000 g for 15 min at 4 • C. The insoluble pellet was discarded and the supernatant was aspirated and considered to be the membrane fraction.…”
Section: Hepatocyte Preparationcontrasting
confidence: 56%
“…Viability of hepatocytes isolated by low speed centrifugation was 89 ± 2.5% by Trypan blue dye exclusion and aliquots were frozen at −80 • C until used. Cytosol and membrane fractions were prepared by centrifugation and differential solubilization in octylglucoside as described by Ruiz-Cortés et al [12]. Purified hepatocytes from the three pigs were thawed on ice, pooled, homogenized by brief exposure to ultrasound in buffer [2 mM octylglucoside, 1 mM DEDTC, 10 mM EDTA in 50 mM Tris, pH 8] and centrifuged at 30,000 g for 60 min at 4 • C. The supernatant (cytosol) was harvested and the particulate fraction was solubilized by ultrasound in 20 mM Tris containing 50 mM EDTA, 0.1 mM DEDTC and 32 mM octylglucoside, and centrifuged at 16,000 g for 15 min at 4 • C. The insoluble pellet was discarded and the supernatant was aspirated and considered to be the membrane fraction.…”
Section: Hepatocyte Preparationcontrasting
confidence: 56%
“…Leptin receptor gene expression in the porcine ovary has been characterized and porcine leptin receptor cDNA has been cloned and sequenced (Ruiz-Cortes et al 2000). Leptin receptor levels are detectable in ovarian follicles collected from prepubertal animals, with a sixfold increase in expression in early antral and antral follicles of cycling animals (Gregoraszczuk et al 2007).…”
Section: Introductionsupporting
confidence: 86%
“…OB-Rb protein expression in OS is also higher on days 10 to 12 than days 14 to 16 (Smolinska et al, 2007a). Similarly, Ruiz-Cortes et al (2000) demonstrated that both gene and protein expression of the leptin receptor peaked in porcine CL during the mid-luteal phase of the cycle, and was the lowest in regressed CL. Furthermore, leptin receptor mRNA increased as the porcine GC luteinized during 96 h in culture.…”
Section: Discussionmentioning
confidence: 99%
“…Leptin mRNA and protein have been identified in humans in GC and theca cells, CL, oocytes and follicular fluid Cioffi et al, 1997;Loffler et al, 2001;Welt et al, 2003); in mice in GC and theca cells, CL, oocytes and OS Ryan et al, 2002); and in rats in theca cells, CL and oocytes (Archanco et al, 2003;Ryan et al, 2003). OB-Rb gene and protein expression has been found in human GC and theca cells (Cioffi et al, 1997;Karlsson et al, 1997;Agarwal et al, 1999); mouse follicular cells, CL, OS and oocytes (Ryan et al, 2002); rabbit and rat follicular cells, CL and oocytes (Zamorano et al, 1997;Ryan et al, 2003); and porcine GC and theca cells harvested from prepubertal gilts, CL and OS (Ruiz-Cortes et al, 2000 andSmolinska et al, 2007a).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation